Margin status and survival outcomes after breast cancer conservation surgery: prospectively registered systematic review and meta-analysis. (21st September 2022) - Bundred, James R; Michael, Sarah; Stuart, Beth; Cutress, Ramsey I; Beckmann, Kerri; Holleczek, Bernd; Dahlstrom, Jane E; Gath, Jacqui; Dodwell, David; Bundred, Nigel J
Abstract: Objective: To determine if margin involvement is associated with distant recurrence and to determine the required margin to minimise both local recurrence and distant recurrence in early stage invasive breast cancer. Design: Prospectively registered systematic review and meta-analysis of literature. Data sources: Medline (PubMed), Embase, and Proquest online databases. Unpublished data were sought from study authors. Eligibility criteria: Eligible studies reported on patients undergoing breast conserving surgery (for stages I-III breast cancer), allowed an estimation of outcomes in relation to margin status, and followed up patients for a minimum of 60 months. Patients with ductal carcinoma in situ only or treated with neoadjuvant chemotherapy or by mastectomy were excluded. Where applicable, margins were categorised as tumour on ink (involved), close margins (no tumour on ink but <2 mm), and negative margins (≥2 mm). Results: 68 studies from 1 January 1980 to 31 December 2021, comprising 112 140 patients with breast cancer, were included. Across all studies, 9.4% (95% confidence interval 6.8% to 12.8%) of patients had involved (tumour on ink) margins and 17.8% (13.0% to 23.9%) had tumour on ink or a close margin. The rate of distant recurrence was 25.4% (14.5% to 40.6%) in patients with tumour on ink, 8.4% (4.4% to 15.5%) in patients with tumour on ink or close, and 7.4% (3.9% to 13.6%) in patients with negative margins. Compared with negative margins, tumour on ink margins were associated with increased distant recurrence (hazard ratio 2.10, 95% confidence interval 1.65 to 2.69, P<0.001) and local recurrence (1.98, 1.66 to 2.36, P<0.001). Close margins were associated with increased distant recurrence (1.38, 1.13 to 1.69, P<0.001) and local recurrence (2.09, 1.39 to 3.13, P<0.001) compared with negative margins, after adjusting for receipt of adjuvant chemotherapy and radiotherapy. In five studies published since 2010, tumour on ink margins were associated with increased distant recurrence (2.41, 1.81 to 3.21, P<0.001) as were tumour on ink and close margins (1.44, 1.22 to 1.71, P<0.001) compared with negative margins. Conclusions: Involved or close pathological margins after breast conserving surgery for early stage, invasive breast cancer are associated with increased distant recurrence and local recurrence. Surgeons should aim to achieve a minimum clear margin of at least 1 mm. On the basis of current evidence, international guidelines should be revised. Systematic review registration: CRD42021232115.